Molecular Mechanisms of Pancreatic Stone Formation in Chronic Pancreatitis - Ko, Shigeru B.; Azuma, Sakiko; Yoshikawa, Toshiyuki; Yamamoto, Akiko; Kyokane, Kazuhiro; Ko, Minoru S.; Ishiguro, Hiroshi (Frontiers in Physiology, 2012)
Chronic pancreatitis (CP) is a progressive inflammatory disease in which the pancreatic secretory parenchyma is destroyed and replaced by fibrosis. The presence of intraductal pancreatic stone(s) is important for the diagnosis of CP; however, the precise molecular mechanisms of pancreatic stone formation in CP were left largely unknown. CFTR is a chloride channel expressed in the apical plasma membrane of pancreatic duct cells and plays a central role in HCO3- secretion. In previous studies, we have found that CFTR is largely mislocalized to the cytoplasm of pancreatic duct cells in all forms of CP and corticosteroids normalizes the localization of CFTR to the proper apical membrane at least in autoimmune pancreatitis. From these observations, we could conclude that the mislocalization of CFTR is a cause of protein plug formation in CP, subsequently resulting in pancreatic stone formation. Considering our observation that the mislocalization of CFTR also occurs in alcoholic or idiopathic CP, it is very likely that these pathological conditions can also be treated by corticosteroids, thereby preventing pancreatic stone formation in these patients. Further studies are definitely required to clarify these fundamental issues.